The Role of 3T Magnetic Resonance Imaging for Targeting the Human Subthalamic Nucleus in Deep Brain Stimulation for Parkinson Disease - Longhi, Michele; Ricciardi, Giuseppe; Tommasi, Giorgio; Nicolato, Antonio; Foroni, Roberto; Bertolasi, Laura; Beltramello, Alberto; Moretto, Giuseppe; Tinazzi, Michele; Gerosa, Massimo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background Chronic stimulation of the human subthalamic nucleus (STN) is gradually becoming accepted as a long-term therapeutic option for patients with advanced Parkinson disease (PD).3Tesla (T) magnetic resonance imaging (MRI) improves contrast resolution in basal ganglia nuclei containing high levels of iron, because of magnetic susceptibility effects that increase significantly as the magnetic field gets higher. This phenomenon can be used for better visualization of the STN and may reduce the time necessary for detailed microrecording (MER) mapping, increasing surgery efficacy and lowering morbidity.Objective The objective of this retrospective study is to analyze a population of 20 deep brain stimulation (DBS) electrode implanted patients with PD divided into two groups in which different targeting methods were used.Methods Mean age was 56 years (range 37 to 69 years). Mean disease duration was 11.6 years. Mean follow-up was 12 months (range 6 to 36 months). Patients were divided into two groups: Group A contained 6 patients who underwent STN targeting using 1T stereotactic (T1w + T2w) MRI plus STN indirect atlas derived targeting. Group B consisted of 14 patients who underwent STN targeting using 3T nonstereotactic (T2w) MRI fused with 1T T1w stereotactic MRI and STN direct targeting. For statistical analysis, we compared (five different parameters in both (matched) groups: Unified Parkinson's disease rating scale (UPDRS) score reduction (medication off before surgery against stimulation on/medication off after surgery), postoperative drug reduction, duration of surgery, the “central preoperative track” chosen as final implantation track during surgery, and correspondence between the targeted STN and the intraoperative neurophysiologic data. Results Mean UPDRS III score reduction (medication off/stimulation on versus preoperative medication off) was 69% in Group A and 74% in Group B (p = 0.015, log-rank test) respectively. Postoperatively, antiparkinsonian treatment was reduced by 66% in Group A and 75% in Group B (p = 0.006, log-rank test). The preoperative “central” track (which corresponds to ideal STN targeting) proved to be the most clinically effective in 2/12 leads for Group A versus 21/28 for Group B (p < 0.001).Neurophysiologic data confirmed these results; the hypothetical target was confirmed by MER data in 76% of tracks in Group A, and in 75% of tracks in Group B (p < 0.001, univariate and multivariate analysis).Conclusion 3T MRI appears to be a useful tool in STN-DBS preoperative targeting. Neurophysiologic testing remains fundamental to determine lead deepness (and prevent clinical side effects.
Keywords: deep brain stimulation; 3-Tesla MRI; subthalamic nucleus targeting